Soluble Epoxide Hydrolase Pharmacological Inhibition Ameliorates Experimental Acute Pancreatitis in Mice - Bettaieb, Ahmed (Mol Pharmacol, 2015)
Acute pancreatitis (AP) is an inflammatory disease, and is one of the most common gastrointestinal disorders worldwide. Soluble epoxide hydrolase (sEH; encoded by Ephx2) deficiency and pharmacological inhibition have beneficial effects in inflammatory diseases. Ephx2 whole-body deficiency mitigates experimental AP in mice, but the suitability of sEH pharmacological inhibition for treating AP remains to be determined. We investigated the effects of sEH pharmacological inhibition on cerulein- and arginine-induced AP using the selective sEH inhibitor 1-trifluoromethoxyphenyl-3-(1-propionylpiperidin-4-yl) urea (TPPU), which was administered before and after induction of pancreatitis. Serum amylase and lipase levels were lower in TPPU-treated mice compared with controls. In addition, circulating levels and pancreatic mRNA of the inflammatory cytokines tumor necrosis factor-α, interleukin Il-1β, and Il-6 were reduced in TPPU-treated mice. Moreover, sEH pharmacological inhibition before and after induction of pancreatitis was associated with decreased cerulein- and arginine-induced nuclear factor-κB inflammatory response, endoplasmic reticulum stress, and cell death. sEH pharmacological inhibition before and after induction of pancreatitis mitigated cerulein- and arginine-induced AP. This work suggests that sEH pharmacological inhibition may be of therapeutic value in acute pancreatitis.